How much efficiency improvement can a spatiotemporal window generate for shared mobility? A case study in New York City. Issue 5 (4th May 2023) - Feng, Pei; Cheng, Yongxi
Abstract : The popularity of shared mobility services has increased in recent years. A complete door-to-door mode is typically deployed. However, the efficiency of the underlying resource utilization is limited in this mode. The space window, a recently developed concept, has the potential to optimize the underlying resource utilization. In this article, the impacts of this concept on the performance of shared mobility in major urban centres, e.g. New York City (NYC), is investigated. To this end, a dynamic routing framework with a spatiotemporal window in L1-norm and a dispatching mechanism are introduced. The operation data demonstrates a 15% reduction of the total distance travelled and the number of vehicles needed if passengers walk a few blocks. These results indicate that a spatiotemporal window holds the promise of a more environmentally friendly, energy efficient and intelligently shared mobility platform with alleviated congestion.